Pemberdayaan Masyarakat Tentang Pentingnya Pembentukan Karakter Tanggung Jawab Sejak Usia Dini (Pengabdian kepada Masyarakat di Desa Cineam, Kecamatan Cineam, Kabupaten Tasikmalaya) - Latip, Iip Muhamad; Robiah, Aas Sholihatur; Millah, Ahlan Syaeful; Anggraeni, Dini; Ashlihatullatifah, Lala; Hapsari, Nuridiah; Rizal, Soni Samsu; Lihayati, Syifa; Yunarti, Uun; Winarti, Widi (Khidmat, 2023)
Community empowerment as an alternative strategy in development has developed in various literature and ideas, including character empowerment in rural communities. Character education also brings people to cognitive recognition of values, affective appreciation of values ​​and finally to real values ​​implementation. This community service aims to empower the community in the area of ​​character, especially responsibility. The method used is Participatory Action Research (PAR) and library research. PAR is a research model that seeks something to connect the research process to the process of social change. This method involves researchers participating in planned changes. The data used is primary data and secondary data as support. This community service produces two community activity programs, the first is taking part in every activity that already exists in the community in order to attract people's interest in participating. The second program is an educational seminar to provide education to the public about the importance of character education and character formation from a young age. The result of these two programs is an increase in the character of responsibility among children and teenagers in rural areas.